Treatment of Large Incisional Hernias in Sandwich Technique - A Review of the Literature - Köckerling, Ferdinand; Scheuerlein, Hubert; Schug-Pass, Christine (Frontiers in Surgery, 2018)
Introduction In a systematic review of the surgical treatment of large incisional hernia sublay repair, the sandwich technique and aponeuroplasty with intraperitoneal mesh displayed the best results. In this systematic review only the sandwich technique, which used the hernia sac as an extension of the posterior and anterior rectus sheath and placement of a non-absorbable mesh in the sublay position, was included. Other modifications of the sandwich technique are published in the literature and were also analyzed in this literature review. Methods A systematic search of the available literature was performed in November 2017 using Medline, PubMed, and the Cochrane Library using the terms “sandwich technique”, “double prosthetic repair”, “double mesh intraperitoneal repair”, and “component separation technique with double mesh”. This review is based on 24 relevant publications. Unfortunately, the evidence of the available studies is not very high since only prospective and retrospective case series have been published. There are no comparative studies at all. Therefore, the findings of the published case series must be viewed in a critical light. Results The published studies report a remarkably low recurrence rate of 0-13% with a follow-up of 1-7 years. One limitation that must be mentioned here is that in around half of the studies the method of follow-up was not specified and in the remaining cases this was based on clinical examination by the surgical team. This puts into perspective the reported results, which appear to be too favorable given the complex nature of the hernias involved. The major disadvantage of the sandwich technique is a very high rate of wound complications of up to 68%, mainly induced by creation of large skin and subcutaneous cellular tissue flaps. Conclusion It is difficult to evaluate the significance of the various modifications of the “sandwich technique” based on the available literature since it includes only case series and no comparative studies. The techniques used are associated with very high wound complication rates but with only relatively low recurrence rates despite the complexity of the cases involved. This must be verified in studies with a well-designed methodology.